2019
DOI: 10.1371/journal.pcbi.1006719
|View full text |Cite
|
Sign up to set email alerts
|

Calcium phosphate precipitation inhibits mitochondrial energy metabolism

Abstract: Early studies have shown that moderate levels of calcium overload can cause lower oxidative phosphorylation rates. However, the mechanistic interpretations of these findings were inadequate. And while the effect of excessive calcium overload on mitochondrial function is well appreciated, there has been little to no reports on the consequences of low to moderate calcium overload. To resolve this inadequacy, mitochondrial function from guinea pig hearts was quantified using several well-established methods inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 62 publications
0
48
0
Order By: Relevance
“…Though P i plays an essential role in matrix Ca 2+ buffering, P i has also been suggested to induce mPTP opening [52]. A recent study associated Ca 2+ –P i precipitation with complex I inhibition and reduced ATP synthase rate during Ca 2+ overload [53]. Another report demonstrated that increasing [P i ] decreased the mitochondrial Ca 2+ loading capacity [14].…”
Section: Discussionmentioning
confidence: 99%
“…Though P i plays an essential role in matrix Ca 2+ buffering, P i has also been suggested to induce mPTP opening [52]. A recent study associated Ca 2+ –P i precipitation with complex I inhibition and reduced ATP synthase rate during Ca 2+ overload [53]. Another report demonstrated that increasing [P i ] decreased the mitochondrial Ca 2+ loading capacity [14].…”
Section: Discussionmentioning
confidence: 99%
“…Animal care and handling conformed to the National Institutes of Health's Guild for the Care and Use of Laboratory Animals and was approved by Michigan State University's Institutional Animal Care and Use Committee. Mitochondria from Hartley guinea pig ventricular myocytes were isolated based on protocol previously described (22,49,65) and will be briefly summarized here. Animals (4-6 weeks, 350-450 grams) were decapitated after being anesthetized with 5% isoflurane and tested to be unresponsive to noxious stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…To test the model's ability to simulate ROS production from intact mitochondria, it was integrated into a recent model of oxidative phosphorylation (49). The integrated model was then used to simulate succinate-dependent leak-state and ADP-stimulated respiration and ROS emission reported in an earlier study (22).…”
Section: Model Testing and Corroborationmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the evidence to date has attributed this effect to inhibition of mitochondrial dehydrogenases, loss of purine nucleotides, and reduced m (Fagian et al, 1986;Lai et al, 1988;Fink et al, 2017). Moreover, a recent study suggested that inhibition of ETC complex I is the most likely cause of the decrease in OXPHOS through accumulation of mitochondrial Ca 2+ as phosphate precipitates (Malyala et al, 2019).…”
Section: Ca 2+ Entry In the Mitochondria And Regulation Of Mitochondrmentioning
confidence: 99%